On the Efficacy of a Platform in a Semi-pelagic Trawl - T., Joseph Mathai; M., Syed Abbas; R.S., Manoharadoss; V., Vijayan (Fishery Technology, 2025)
Fishing performance of a 20m semi-pelagic trawl additionally equipped with a platform panel as a forward extension of lower belly, has been evaluated in this paper, based on comparative field trials with a control gear, from a 10.9m LOA wooden trawler (65 hp) in the waters off Mormugao. Significant improvement in the catch of quality fishes by 68.4% (p